Efektivitas Game Based Learning Berbantuan Kahoot Dalam Meningkatkan Minat dan Hasil Belajar Siswa Kelas X TITL SMKS Raden Paku - Khovivatul Qolby; Tri Rijanto; Nur Kholis; Fendi Achmad (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to determine (1) the interests in the subjects DDTK of students of X TITL SMKS Raden Paku before and after the implementation of Game Based Learning with the help of the Kahoot application; (2) the learning outcomes in the subjects DDTK of the students of the X-TITL of SMKS Paku Raden before and following the application of Game based learning with the aid of the kahoot app. The design of one group pretest-posttest is the experimental methodology used in this study. The researchers involved the entire class X TITL SMKS Raden Paku as a population. Techniques to test students' interests and learning outcomes are test and lifting techniques. The results of this study showed that the interest and learning outcomes of students of X grade TITL SMKS Raden Paku before and after the treatment with Game Based Learning assisted by Kahoot increased. This is demonstrated by the pre-test averages of 48.89 and 58.30 and the posttest averaging of 84.09 and 82.50. The results of both hypothesis tests showed that the significance value was 0,000 < 0.05, which means Ha was accepted. The N-gain test of learning interest and learning outcomes indicated that the average N-gein score was 0.683 and 0.616 which meant effectiveness in the medium category. This indicates that the application of Game Based Learning with the help of Kahoot is quite effective in increasing the interests and learning outcomes in the subjects DDTK of X grade students of SMKS TITL Raden Paku.